2012
DOI: 10.5714/cl.2012.13.1.034
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy study on the reactions of UV-generated oxygen atoms with single-layer graphene on SiO2/Si substrates

Abstract: Successful application of graphene requires development of various tools for its chemical modification. In this paper, we present a Raman spectroscopic investigation of the effects of UV light on single layer graphene with and without the presence of O 2 molecules. The UV emission from a low pressure Hg lamp photolyzes O 2 molecules into O atoms, which are known to form epoxy on the basal plane of graphene. The resulting surface epoxy groups were identified by the disorder-related Raman D band. It was also fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…We have seen in separate experiments that exposure to the flux of oxygen atoms, molecules, and radicals in a plasma environment increases the resistance by more than 3 orders of magnitude. The strong effect of atomic oxygen is consistent with previous reports 12,15,[23][24][25] but does point out that using an O 2 plasma ashing step to remove photoresist residues is not benign. The UV ozone environment is much more benign but still can degrade the electrical properties of graphene for extended exposures.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…We have seen in separate experiments that exposure to the flux of oxygen atoms, molecules, and radicals in a plasma environment increases the resistance by more than 3 orders of magnitude. The strong effect of atomic oxygen is consistent with previous reports 12,15,[23][24][25] but does point out that using an O 2 plasma ashing step to remove photoresist residues is not benign. The UV ozone environment is much more benign but still can degrade the electrical properties of graphene for extended exposures.…”
Section: Resultssupporting
confidence: 90%
“…12 Robinson et al 12 investigated the properties of a number of different contacts to graphene (Al/Au, Ti/Au, Ni/ Au, Cu/Au, Pt/Au, and Pd/Au) and found that most metallizations resulted in similar specific contact resistances independent of the work function difference between graphene and the metal overlayer. In any practical processing sequence, the graphene surface will be exposed to different chemicals, such as photoresist residues, 13,14 oxygen atoms, 15 and even adsorption of water molecules, which have been shown to significantly influence the resistivity of the graphene. [16][17][18] Thus, conventional lithographic processing for graphene devices needs careful attention to avoid degrading the surface properties.…”
Section: Introductionmentioning
confidence: 99%
“…9 Due to its electronic structure and high surface to volume ratio, the electronic properties of graphene are highly sensitive to chemical interactions with its environment. 10,11 As a consequence, some conventional lithographic processing for nanoelectronic devices adversely affect graphene surface properties, including exposure to oxygen atoms, 12 presence of photoresist residues, 13,14 and adsorption of water molecules. 15,16 In particular, it is found that O 2 plasma treatments can improve contact resistances and adhesion for metals on graphene by removing photoresist residues and making the surface hydrophilic.…”
Section: Introductionmentioning
confidence: 99%